Polyprenols Are Synthesized by a Plastidial cis-Prenyltransferase and Influence Photosynthetic Performance. Issue 7 (27th June 2017) - Akhtar, Tariq A.; Surowiecki, Przemysław; Siekierska, Hanna; Kania, Magdalena; Van Gelder, Kristen; Rea, Kevin A.; Virta, Lilia K.A.; Vatta, Maritza; Gawarecka, Katarzyna; Wojcik, Jacek; Danikiewicz, Witold; Buszewicz, Daniel; et al.
Abstract : A plastidial cis -prenyltransferase synthesizes a family of polyprenols that accumulate in thylakoid membranes and play a central role in the efficiency of photosynthetic performance. Abstract: Plants accumulate a family of hydrophobic polymers known as polyprenols, yet how they are synthesized, where they reside in the cell, and what role they serve is largely unknown. Using Arabidopsis thaliana as a model, we present evidence for the involvement of a plastidial cis -prenyltransferase (AtCPT7) in polyprenol synthesis. Gene inactivation and RNAi-mediated knockdown of AtCPT7 eliminated leaf polyprenols, while its overexpression increased their content. Complementation tests in the polyprenol-deficient yeast ∆rer2 mutant and enzyme assays with recombinant AtCPT7 confirmed that the enzyme synthesizes polyprenols of ∼55 carbons in length using geranylgeranyl diphosphate (GGPP ) and isopentenyl diphosphate as substrates. Immunodetection and in vivo localization of AtCPT7 fluorescent protein fusions showed that AtCPT7 resides in the stroma of mesophyll chloroplasts. The enzymatic products of AtCPT7 accumulate in thylakoid membranes, and in their absence, thylakoids adopt an increasingly "fluid membrane" state. Chlorophyll fluorescence measurements from the leaves of polyprenol-deficient plants revealed impaired photosystem II operating efficiency, and their thylakoids exhibited a decreased rate of electron transport. These results establish that (1) plastidial AtCPT7 extends the length of GGPP to ∼55 carbons, which then accumulate in thylakoid membranes; and (2) these polyprenols influence photosynthetic performance through their modulation of thylakoid membrane dynamics.